2008
DOI: 10.1007/s11668-008-9148-3
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis of Induction Hardened Automotive Axles

Abstract: Rollover accidents in light trucks and cars involving an axle failure frequently raise the question of whether the axle broke causing the rollover or did the axle break as a result of the rollover. Axles in these vehicles are induction hardened medium carbon steel. Bearings ride directly on the axles. This article provides a fractography/ fracture mechanic approach to making the determination of when the axle failed. Full scale tests on axle assemblies and suspensions provided data for fracture toughness in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The fatigue damage tolerance therefore takes into account not only the minimum crack size detectable using NDT methods but also suitable intervals between inspections, set depending on the location and period of operation. In addition to these basic design concepts, studies also focus on the effects of structural materials, surface treatments, methods of heat treatment and subsequent machining, and geometric parameters – particularly the effect of axle body diameter and wheel seat diameter on fatigue strength with a focus on high‐speed train axles . One technology applied to increase axle fatigue strength is surface induction hardening, which involves the relatively rapid heating of surface layers of pre‐machined axles up to the hardening temperature using an inductor, followed by the rapid cooling of the axle by a water jet positioned behind the inductor and also by the transfer of heat by the axle body.…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue damage tolerance therefore takes into account not only the minimum crack size detectable using NDT methods but also suitable intervals between inspections, set depending on the location and period of operation. In addition to these basic design concepts, studies also focus on the effects of structural materials, surface treatments, methods of heat treatment and subsequent machining, and geometric parameters – particularly the effect of axle body diameter and wheel seat diameter on fatigue strength with a focus on high‐speed train axles . One technology applied to increase axle fatigue strength is surface induction hardening, which involves the relatively rapid heating of surface layers of pre‐machined axles up to the hardening temperature using an inductor, followed by the rapid cooling of the axle by a water jet positioned behind the inductor and also by the transfer of heat by the axle body.…”
Section: Introductionmentioning
confidence: 99%
“…Roland et al [7] and Yang et al [8] showed that a stainless steel with surface mechanical attrition treatment and a pure Cu with surface mechanical grinding treatment had higher fatigue strength than the original materials, especially in high cycle fatigue regime. Other articles [10][11][12][13][14][15] also reported similar results of different materials with various types of surface treatments. All these investigations attributed the enhancement of the fatigue strength for the treated specimens or components to the grain refinement and the compressive residual stress caused by surface strengthening treatment.…”
Section: Introductionmentioning
confidence: 67%
“…According to Eqs. (10) and (11), both the loading level and the material properties influence the value of plastic zone size and crack opening displacement. The estimations showed that, under the same loading condition, the value of r p at 3 mm depth is 2.5 times of that at 2 mm depth and the value of δ at 3 mm depth is 1.5 times of that at 2 mm depth, respectively, which means that the plastic zone size and the crack opening displacement increase rapidly as the fatigue crack growing through the gradient layer (from hardened surface gradually to the original microstructure).…”
Section: Crack Tip Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…The region of crack initiation and fatigue crack growth is the flat, oval-shaped region at the case-core interface (arrows in Figures 31(a) and 31(b). Surface nucleated failures are also possible in bending fatigue (39), but compressive residual stresses at the surface and the comparatively weak core microstructure make subsurface crack nucleation more likely. Radial marks point back to the crack initiation location.…”
Section: Fatigue Fracture Surface Location and Morphologymentioning
confidence: 99%